Screening and Characterization of Bacteriocin-Like Inhibitory Substances Produced by Bangladeshi Strains of Bacillus thuringiensis - Islam, Md Nahidul; Akhand, Nahinur Rahman; Mamun, Arafat Al; Shishir, Asaduzzaman; Aktar, Marufa Zerin; Khan, Shakila Nargis; Hoq, Md Mozammel; Hossain, Mohammad Shahnoor (Bangladesh Pharmaceutical Journal, 2015)
Bacteriocins are ribosomally synthesized antibacterial peptides which have the potential to be used as natural food preservatives as well as alternative to antibiotics. Here, we report the production of bacteriocin-like inhibitory substances (BLIS) from the indigenous strains of Bacillus thuringiensis. Deferred antagonism bacteriocin assay and agar well diffusion methods suggested that several of the tested strains have high levels of bacteriocin-like activity against the common food-borne pathogens, Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus. These bacteriocins are generally produced at the mid-logarithmic phase of growth with optimum temperature of 37 ºC, pH-7.0 and 24 h of incubation. Heat stability assay demonstrated that the bacteriocins produced from the strains are highly heat stable and can retain activity up to 100 ºC. Our study suggests that these bacteriocins may be potential candidates for use as biodegradable natural food preservatives and alternative antimicrobial agents to solve the increasing trends of problems of antibiotic resistance. Bangladesh Pharmaceutical Journal 18(2): 149-156, 2015